Seasonal effects on spatial variations of surface water quality in a tropical river receiving anthropogenic influences - Tengku Nilam Baizura Tengku Ibrahim,; Faridah Othman,; Noor Zalina Mahmood,; Abunama, Taher (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigates the seasonal and spatial water quality patterns along a tropical river that continuously receives various pollution sources. Multivariate analysis was used to study the spatial and temporal variations of the water quality parameters and to determine the origin of the pollution sources. Three regions (low, moderate, and high pollution levels) were determined based on cluster analysis. The stepwise DA mode proposed six parameters (pH, EC, COD, NO3 , TC, and Fe) with 75% correct assignations as the most significant water quality parameters to present the spatial variations. In the temporal discrimination, forward stepwise mode analysis showed eight parameters (EC, TUR, BOD, COD, AN, NO3 , Cu, and Cr) with 92% correct assignations, while five parameters (EC, AN, Al, Cu, and Cr) affording 89% correct assignations in backward stepwise mode analysis. Principal component analysis and factor analysis were used to investigate the origins of each water quality parameter based on the three clustered regions and successfully yielded eight latent factors loadings for each period that significantly identified the pollution sources and types along the river. The pollution sources for moderate and high pollution level areas are anthropogenic sources (landfill, industrial activities, and sewage discharge). Agricultural runoff is the main pollution source for the low pollution level areas. This study has shown classifications of river water quality based on seasonal and spatial criteria.